AUTOCLAVE DEVICE: DEVELOPMENT OF A NEW STRUCTURE FOR THERMAL, PRESSURE, AND SAFETY ELEMENTS (International journal of artificial intelligence, 2025)
This article presents a comprehensive study on the development of a novel autoclave device incorporating an advanced structure for thermal, pressure, and safety elements. The research addresses the limitations of conventional autoclave systems, including uneven heat distribution, pressure instability, and potential safety hazards during sterilization processes. By integrating state-of-the-art thermal sensors, adaptive pressure control mechanisms, and redundant safety elements, the proposed autoclave design ensures precise and uniform sterilization while significantly reducing operational risks. The study details the engineering principles, structural innovations, and testing procedures employed to validate the device’s performance. Experimental results demonstrate improved temperature consistency, stable pressure regulation, and enhanced safety protocols, confirming the device’s reliability for biomedical, laboratory, and industrial sterilization applications. Furthermore, the proposed design offers scalability, energy efficiency, and potential integration with automated monitoring systems, paving the way for next-generation autoclave technologies that meet modern safety standards and operational requirements.